Coming to terms Indochina, the United States, and the War (Westview Press, 1991)
The book presents an accessible overview from both the Indochinese and antiwar perspectives. It traces the prewar history, war years, and postwar experience, where it focuses on government policies, the antiwar movement, veterans, and films and literature on VietNam